ISSUES OF IMPROVING THE TAX ADMINISTRATION THROUGH THE FORMATION OF INFORMATION IN THE ELECTRONIC DOCUMENT CIRCULATION SYSTEM - Muxammadov Nodir Karimovich (Research Parks Publishers, 2023)
In the articlein order to accelerate the transition of the tax system to the digital economy, the set of information systems of tax authorities is being transferred to a fully unified platform. As a result, data entry, collection, and analysis systems will be optimized, taxpayers' reporting process will be simplified by 5-7 times, human factor intervention will be reduced by 60%, opportunities will be created to create a completely new system of tax administration and control, as well as prevent corruption factors